2019
DOI: 10.1038/s41440-019-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-based perivascular unilateral renal sympathetic nerve denervation for treating resistant hypertension: a case report

Abstract: A 38-year-old man with a history of resistant hypertension for more than 10 years underwent laparoscopic-based perivascular unilateral renal sympathetic nerve denervation in 2012. After the operation, the patient's blood pressure has been controllable while the antihypertensive drug intake has decreased over 6 years. Laparoscopic-based perivascular unilateral renal sympathetic nerve denervation may be a potentially feasible and effective option in treating patients with resistant hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…One case showed that even unilateral RDN can be fully successful and decrease BP to a remarkable extent in a 12-month period [ 27 ]. Gao et al reported considerable BP decrease with laparoscopic-based perivascular unilateral RDN [ 28 ]. In an animal model, unilateral RDN improved mean arterial pressure and cardiac autonomic balance in congestive heart failure by reducing sympathetic tone [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…One case showed that even unilateral RDN can be fully successful and decrease BP to a remarkable extent in a 12-month period [ 27 ]. Gao et al reported considerable BP decrease with laparoscopic-based perivascular unilateral RDN [ 28 ]. In an animal model, unilateral RDN improved mean arterial pressure and cardiac autonomic balance in congestive heart failure by reducing sympathetic tone [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we believed that direct stimulation using RF energy and the use of catheter and wire on the arterial intima could result in intimal injury and/or thrombosis, 13,24 which may trigger the progression of atherosclerosis. Moreover, an inappropriate ablation device may lead to inadequate ablation, which in turn results in uncertainty in the effects of RDN 14 …”
Section: Discussionmentioning
confidence: 99%
“…A case study reported by our team showed that laparoscopic‐based RDN from the adventitia of renal artery could effectively treat resistant hypertension 14 . In that report, our team for the first time used laparoscopic RDN from the adventitia of renal artery for resistant hypertension.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, novel neuromodulation approaches targeting sympathetic nerve inhibition might be potential for the treatment of resistant hypertension. Tremendous evidences have proved that neuromodulation techniques such as functional electrical stimulation (FES) of the carotid baroreceptor (Scheffers et al, 2010;Bisognano et al, 2011;Lohmeier and Iliescu, 2011;Bakris et al, 2012;Hoppe et al, 2012)/vagus nerve (Plachta et al, 2014;Gierthmuehlen et al, 2016;Annoni et al, 2019) and renal sympathetic denervation (RSD) by different devices and techniques [including surgical sympathectomy (Smithwick, 1948), laparoscopic sympathectomy (Gao et al, 2019), catheterbased radiofrequency ablation (Krum et al, 2009), endovascular ultrasound (Fengler et al, 2019), injection of neurotoxic agents (Lohmeier and Hall, 2019), external stereotactic radiofrequency (Cai et al, 2019), external high-intensity focused ultrasound (Wang et al, 2013), etc.,] might reduce BP through sympathetic nerve activity inhibition. However, these procedures of current neuromodulation methods are either invasive or associated with complete nerve damage.…”
Section: Introductionmentioning
confidence: 99%